Graphical determination of earth slopes, retaining walls and dams - Prelini, Charles (Archibald Constable, 1908)
The greater part of this work consists of graphical methods of solving problems concerning the slopes of earth embankments, the lateral pressure of earth against a wall, and the thickness of retaining walls and dams.